On- and Off-Farm Diversification and Travel Time to Markets: Linkages to Food Security in Rural Ethiopia - Sven Bergau; Tim K. Loos; Orkhan Sariyev (The European Journal of Development Research, 2021)
Food insecurity persists in large parts of Ethiopia. Recent literature suggests that both on-farm and off-farm diversification, as well as access to agricultural markets, may help improve household dietary diversity scores (HDDS) as an indicator for food and nutrition security. While the HDDS is frequently used, a diversity score for the production side has rarely been applied at a comparable level of (dis-)aggregation. Employing socio-economic data collected covering 400 Ethiopian smallholder farmers, this study investigates how the travel time to markets, non-farm income, and on-farm production diversity associate with household food and nutrition security. Findings suggest that production diversity and higher non-farm income are linked to more diverse diets. With longer travel time to markets, food consumption is less varied. Production diversity and increased market participation do not appear to be mutually exclusive, and thus, should be considered equally when developing policy interventions.
Keywords: 330; Income diversification; Production diversity; Market access; Dietary diversity; Ethiopia